Social media coverage of developments in the Palestinian cause. (Operation Tufan of Al-Aqsa) and its role in activating relief and humanitarian support activities. (Facebook "Meta" as an example). (Al-Mansour Journal, 2025)
This study deals with the analysis of the digital content of pages and sites that support the Palestinian cause on social media platforms،Specifically Facebook (Meta) in the context of Operation Al-Aqsa Flood, the study aims to highlight how these pages use social media as an effective tool in spreading awareness and stimulating international solidarity, and organizing protest activities The study was based on the analysis of a sample of Palestinian, Arab and international pages that dealt with the events of Operation Al-Afsa Flood and its various roles in strengthening digital resistance and spreading humanitarian stories and political analysis She also reviewed the challenges faced by these pages, such as censorship and restriction by Facebook's management.The results of the study showed that these pages are used successfully in publishing visual and documentary content that highlights the suffering of Palestinians. It also enhances international and local interaction through organizing solidarity campaigns and the use of unified hashtags. The study confirmed that social media has become an important element in Palestinian digital resistance, as it contributes to overcoming traditional media barriers and communicating the Palestinian narrative to a wider global audience.
Keywords: social media sites; The Palestinian question; Tufan Al-Aqsa